Integrating Functional and Phylogenetic Diversity to Assess Bird Community Assembly Along the Major Rivers of Hainan Island, South China - Sidan Lin; Wei Liang (Ecology and Evolution)
ABSTRACT Understanding the mechanisms associated with community assembly can contribute to explaining the formation and maintenance of biodiversity patterns. In this study, we used the line transect method to survey breeding birds along the three major rivers of the Nandu River, Changhua River and Wanquan River on Hainan Island, south China. The patterns of community assembly were subsequently assessed by integrating functional and phylogenetic diversity, whereas environmental factors and interspecific competition intensity were incorporated to determine whether community assembly in these rivers is driven by environmental filtering or interspecific competition. Our findings revealed that bird communities within rivers were characterized by an overall slight clustering (i.e., more similar species), with the upper reaches of the Changhua River and the lower reaches of the Nandu River showing over‐dispersion, whereas the lower, middle, and upper reaches of the Wanquan River all showed clustering. Altitude and the human influence index were identified as the main factors driving bird community assembly within the three major rivers. Notably, for bird communities along different river reaches, the integration of functional and phylogenetic diversity prevented the mis‐classification of over‐dispersion or clustering in community structure caused by traits with weak phylogenetic signals, or the observation of traits unrelated to community assembly patterns. This empirical study demonstrates the importance of integrating functional and phylogenetic diversity, which not only contributes to gaining an understanding of the mechanisms underlying the development of community assemblies but also facilitates a determination of the extents to which function and phylogeny contribute to shaping the patterns of communities.